Evaluation of the Smear Layer and Hybrid Layer in Noncarious and Carious Dentin Prepared by Air Abrasion System and Diamond Tips - Mascarenhas Oliveira, Ana Carolina [UNESP]; Lima, Luciana Monti [UNESP]; Pizzolitto, Antonio Carlos [UNESP]; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP] (Wiley-liss, 2010)
Purpose: To analyze the smear layer and the hybrid layer in noncarious and carious dentin prepared by different cutting instruments and restored with composite resin. Study design: Cavities were randomly prepared in 160 specimens (noncarious and artificial carious dentin) by high-speed diamond tips (KG Sorensen 1013), air abrasion system (Prepstart, Danville Engineering), ultrasonic tip (CVDentus 8.3231-1), and ultrasonic tip associated with ultrasonic cavitation by water for 10 s. Half of the cavities in each group were conditioned with 37% phosphoric acid for 15 s. The amount of smear layer and dentinal tubules present were analyzed using scanning electron microscopy and graded from 0 to 3. Cavities were prepared in another 20 noncarious specimens and 20 carious specimens and restored with adhesive composite resin system. The restorations were hemisected longitudinally and analyzed using scanning electron microscopy to evaluate the hybrid layer and resinous prolongation characteristics, using scores ranging from 1 to 6. Results: The data were statistically analyzed using Kruskal-Wallis and Dunn tests at 5% of significance level. There was evidence that the most efficient smear layer removal was the acid etching in the noncarious dentin and the water ultrasonic cavitation in the carious dentin. The hybrid layer formed on the noncarious and carious dentin prepared by the ultrasonic tip was more regular than in the specimens prepared by high-speed diamond tip, with many resinous prolongations. Conclusion: The ultrasonic tip seems to be a promising tool for carious dentin cavity preparation. Microsc. Res. Tech. 73:597-605, 2010. (C) 2009 Wiley-Liss, Inc.
Keywords: preparation of the dental cavity; abrasion system; ultrasonic tips; high-speed tips